2021
DOI: 10.1051/e3sconf/202131901055
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of food poisoning during the period 2001-2018 in the province of Kenitra

Abstract: Foodborne illnesses can be the cause of morbidity or mortality. Collective foodborne illnesses (TIAC) are generally benign; their epidemic nature can have a significant impact in terms of public health and socio-economic aspects. The present study intends to establish a database inherent to food poisoning specific to the province of Kenitra during the period 2001-2018. These data will help inform about the current situation and the epidemiological evolution during the summer seasons of the study period. This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…In a similar study in Kenitra, Morocco, 43 foodborne disease outbreaks were reported between 2001 and 2018, affecting 367 poisoned individuals, including 69 hospitalized and 2 death cases. In that study, 25% of the samples revealed the presence of Salmonella (Elkhal et al, 2021). DOI: https://dx.doi.org/10.…”
Section: Introductionmentioning
confidence: 72%
“…In a similar study in Kenitra, Morocco, 43 foodborne disease outbreaks were reported between 2001 and 2018, affecting 367 poisoned individuals, including 69 hospitalized and 2 death cases. In that study, 25% of the samples revealed the presence of Salmonella (Elkhal et al, 2021). DOI: https://dx.doi.org/10.…”
Section: Introductionmentioning
confidence: 72%
“…This is most likely to occur when an ill person prepares food and doesn't wash their hands before cooking.Meat, eggs, and dairy products are frequently contaminated. Water may also be contaminated with organisms that cause illness [2]. When a case of acute gastroenteritis, presenting with combinations of the main abdominal pain symptoms, diarrhea and vomiting in at least two patients sharing a common meal, then it can be readily associated with the suspicion of an episode of a food poisoning [3].…”
Section: Introductionmentioning
confidence: 99%